Da colônia ao shopping: um estudo da evolução tipológica da arquitetura hospitalar em Natal - Medeiros, Maria Alice Lopes (2005)
A conceptual discussion on architectural type and its role in theory and practice supports the construction of an analytical tool used for recognizing the typological evolution of hospital architecture in Western societies. The same tool is applied to analyze the typological evolution of hospital architecture in Natal, Brazil, through a sample of eighteen hospitals built in the city since the beginnings of 20th century. The conclusion is that typological evolution in Natal is almost the same as occidental one, except for a few singularities that can be explained by local social and economic development